Exploring the Effects of Digital Game-Based Learning on Music Education - Chun Qian; Mingke Jiang (Studies in Social Science & Humanities, 2024)
Digital game-based learning (DGBL) has been proven its potential and benefits in educational fields, including musical education. Yet, there remains a paucity of robust quantitative evidence on the effects of DGBL on enhancing students’ piano performance, particularly in Chinese tertiary levels. Therefore, this current research aims to conduct a quasi-experimental design to investigate the impact of DGBL on Chinese university students’ piano performance. Participants were recruited in a southern Chinese university with 30 intermediate-level piano major students. Whilst the experimental group received the DGBL during classes, the control one used the traditional method to learn piano. Quantitative findings showed that the posttest of the experimental group students was higher than their pretest. Moreover, students from the experimental group performed better than the control group. This study may shed some light on implicational practices for teachers and educators with regard to using DGBL to teach students piano.